ANALYSIS OF THE DETERMINING FACTORS OF HEALTH OF COVID PATIENTS THERAPED WITH FAVIPIRAVIR IN THE ISOLATION CARE ROOM OF THE PENDAU TAMBU HOSPITAL - Junaedi, Nafira; Wirapuspita Wisnuwardani, Ratih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The coronavirus disease pandemic of 2019 (Covid-19) continues to be a serious worldwide health issue. The virus quickly spread to other nations after the first case was discovered in Wuhan, Hubei Province, China in the afternoon of 2019. On March 11, 2020, the World Health Organization proclaimed COVID-19 a global epidemic.. 1 Covid report in Indonesia Indonesia ranks 64th compared to countries in the world, until December 2022 showing 6,719,815 cases.2 The daily report of Covid-19 in districts and cities in Central Sulawesi Province on April 7, 2021, the total number of positive confirmed cases was 11,424 cases. As of September 9, 2022, the number of confirmed positive cases of Covid- 19 in Donggala Regency reached 2,678 people, 77 cases of death due to Covid-19.3 Favipiravir is advised as a treatment for COVID-19 patients with mild to serious symptoms by the Indonesian Medical Association. 1 Favipiravir has an emergency use authorization (EUA) from the Indonesian National Food and Drug Administration for hospitalized patients with mild to moderate COVID-19 signs and symptoms. 4 Early COVID- 19 antiviral trials conducted in China documented the administration of 1,600 mg of oral favipiravir twice daily on the first day, and then another 1,600 mg of oral favipiravir twice daily after that. In contrast to the Thai trial, which found that favipiravir was not more successful in treating severe Covid-19 sufferers, 600 mg twice daily produced superior results. 56 There are still many other studies that discuss this treatment regarding the effectiveness of Favipiravir against COVID-19, but this is still a debate because it still raises pros and cons. In Indonesia and especially in Central Sulawesi, data on the effectiveness of using favipiravir in COVID-19 patients is still limited. Objective : This study aims to evaluate the effect of giving favipiravir antiviral drugs to COVID-19 patients on the recovery of patients treated at Pendau Tambu Hospital in 2021-2022. Research Methods/ Implementation Methods : This study is cross-sectional in nature and employs a cross-sectional design with retrospective data and an analytical observational methodology. The medical records of COVID-19 patients who were admitted to Pendau Tambu General Hospital between June 2021 and March 2022 provided the secondary data for this investigation. In order to meet the sample size requirement of 57 samples, the study's sample selection strategy involved enrolling all patients who satisfied the inclusion criteria. Adult patients who are at least eighteen years old and hospitalized COVID-19 patients receiving favipirafir therapy meet the inclusion criteria. antiviral medication during therapy, and the medical record data was incomplete. Results : A total of 57 patients who met the criteria, patient characteristics (table1) most of the patients were under 60 years of age, gender was generally the same in men and women, most did not have high blood pressure and did not have comorbidities, and the final condition of discharge patients generally recovered. The results of the chi square test found the value of 2 cells (50%) Expectation is less than 5 so it cannot test with chi aquare, and the data is statistically tested using fisher's exact test. Based on Table 2, it can be seen that all characteristics of the research subjects have no relationship